Determination of Policies for Covid-19 PPE Using for URM Hospital Employees During The Pandemic - Ramadhany, Nur Azizha; Prasetya, Jaka; Agiwahyuanto, Faik (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Background: Policies regarding procedures for using Personal Protective Equipment (PPE) for medical record officers were needed during the Covid-19 pandemic. This study aims to analyze the quality assurance of services in the medical record unit RSUP Dr. Kariadi Semarang in the era of the Covid-19 pandemic. Type of mixed methods research. Methods: Type of mixed methods research. This research was conducted from July 1 to August 15, 2020. The data were obtained through in-depth interviews, and the processing and analysis of research data were carried out using content analysis and quantitative methods. Results: RSUP Dr. Kariadi Semarangalready have an SOP for the procedure for using Personal Protective Equipment (PPE) for medical record officers during the Covid-19 pandemic. Officers comply with the SOP for using Personal Protective Equipment (PPE) during the pandemic. Conclusions: There has been an evaluation of hospital policy monitoring the use of PPE for medical record officers in the Covid-19 pandemic era. KEYWORDS: Policies; Personal Protective Equipment (PPE); URM; Covid-19 pandemic era